Penilaian Komparatif Kinerja Keuangan Rasio Profitabilitas dan Nilai Tambah Ekonomi (EVA) pada Perusahaan Indeks MNC35 - Vaisal Amir; Dewi Kirowati; Niza Nurmalasari (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to analyze the financial performance of major companies in Indonesia using the Economic Value Added (EVA) approach as an indicator of value creation. The companies examined include PT Astra International Tbk (ASII), PT Bank Central Asia Tbk (BBCA), PT Bank Negara Indonesia (Persero) Tbk (BBNI), PT Bank Rakyat Indonesia (Persero) Tbk (BBRI), PT Bank Mandiri (Persero) Tbk (BMRI), PT Media Nusantara Citra Tbk (MNCN), PT Bukit Asam Tbk (PTBA), and PT Aneka Tambang Tbk (ANTM). EVA is calculated using data on Net Operating Profit After Tax (NOPAT), Invested Capital (IC), and the Weighted Average Cost of Capital (WACC). The results show that most companies generated positive EVA, creating shareholder value. BBCA, BBRI, and BMRI recorded the highest EVA, reflecting effective capital utilization and sound business strategies. On the other hand, ANTM posted a negative EVA, suggesting that its capital cost exceeded its net operating profit. These findings offer valuable insights for investors and corporate management in assessing financial efficiency and making strategic decisions focused on long-term value creation.